PERSPECTIVES OF TECHNICAL EDUCATION DEVELOPMENT FOR STUDENTS WITH MILD MENTAL DISABILITIES - BARTON, Ales (Journal of Technology and Information Education, 2017)
This paper deals with possible perspectives for the educational area Man and the World of Work, resulting from the gradual introduction of common education. Some of them were described by means of the content analysis and subsequent comparison of the Framework Education Programme for Elementary Education (2016), other information sources and the already expired Annex modifying the education of pupils with mild mental disabilities (2005). For the purposes of exploratory survey the quantitative approach was used, whereby it was found that the inclusive education affects amount of the time allocation for the educational area Man and the World of Work.
Keywords: available time allocation; key competencies; light mental disability; expected outputs; supportive measures; joint education (inclusion).